The impact of the creation of a sovereign ESG reference yield curve on corporate ESG bonds issuances from Latin America and the Caribbean - Daniel Cunha; Giovana Craveiro; Marina Rossi (Inter-American Development Bank (IDB), 2024)
This paper explores a granular database from the Inter-American Development Bank (IDB) Green Bond Transparency Platform covering the issuance of 430 corporate and sovereign Environmental, Social, and Governance (ESG) bonds in Latin America and the Caribbean (LAC) that are outstanding in international markets. The goal was to investigate how the creation of a sovereign ESG reference yield curve can boost the private ESG bond market. Using a difference-in-differences (DID) approach, we empirically estimate that the creation of a sovereign ESG reference curve roughly leads to a 60 percent increase in the volume of corporate bond issuances and a 25 percent increase in the number of ESG corporate bond issuances in the external markets after three years. On the mechanisms, we argue that the sovereign ESG reference yield curve works as a benchmark for private sector ESG bond issuers by providing a standard against which the performance of ESG bonds can be measured.
Keywords: H63; E43; R50; 330; ESG; thematic bond; green; social; sustainability; sustainability-linked bond; debt capital markets; sovereign debt; LAC; corporate sector; international markets